Histohub software is a way to improve the learning of medical students - Zeynab Gholamnia-Shirvani; Zeynab Hosseini-Motlagh; Leyla beygom Hejazian; Maryam Ghaemi-Amiri; Zahra Babazadeh (Babol University of Medical Sciences, 2023)
Background & Objective: Considering the complexity and variety of histological concepts and the positive impact of virtual systems on the teaching of this course, a study was conducted to design, implement, and evaluate the Histohub software in medical students. Materials and Methods: A semi-experimental study was conducted on Babol University of Medical Sciences students in 2021. The educational content of the Histohub software was designed based on the approved subject of the histology course in the form of electronic files using PowerPoint, Camtasia, and V-Recorder. The effect of the educational software on students' satisfaction and learning was evaluated using a valid and reliable satisfaction questionnaire and the final test scores of the histology course. The data was described by SPSS21 software. Results: In this study, 90 medical students with an average age of 20.04±1.59 participated. The total satisfaction questionnaire score was 25.4 ± 4.7 (out of 30 points). The item related to "learning improvement" by the Histohub had the highest score (4.42±0.73) and "learning continuity" had the lowest score (4.15±0.86) out of 5 points. The highest score in the histology course (18.54±2.31) out of 20 scores was related to medical students. Conclusion: Teaching histology using the Histohub software can improve the level of satisfaction and learning of medical students, which can be included in the combined teaching of this course.